Surface protective film
Patent Information
- Application Number
- JP2022078026
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-05-11
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2042-05-11
AI Technical Summary
Existing surface protection films for optical and electronic components lack sufficient antistatic properties and easy releasability, leading to potential damage, static electricity issues, and contamination during manufacturing processes.
A surface protection film with a base layer, antistatic layer, and adhesive layer, where the adhesive layer contains a urethane prepolymer and a fluorine-based compound, along with optional ionic compounds, to provide excellent antistatic properties and easy peelability, minimizing static electricity and contamination.
The film effectively prevents scratches and static electricity, ensuring easy and stable peeling without contamination, maintaining the integrity of optical and electronic components during processing and assembly.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a surface protection film. [Background technology]
[0002] In the manufacturing process of optical and electronic components, a surface protection film is generally applied to the exposed surfaces of the optical and electronic components to prevent the surfaces of the optical and electronic components from being damaged during processing, assembly, inspection, transportation, etc. Such a surface protection film is peeled off from the optical and electronic components when surface protection is no longer necessary (Patent Document 1).
[0003] Optical and electronic components are generally expensive and easily damaged, and therefore, a surface protection film attached to the exposed surface of an optical or electronic component is required to have excellent easy releasability so as not to damage the optical or electronic component when peeled off.
[0004] Furthermore, surface protection films, optical components, and electronic components typically have high electrical insulation properties and generate static electricity due to friction or peeling. Therefore, static electricity is likely to be generated when peeling a surface protection film from an optical component or electronic component. In such cases, for example, if a voltage is applied to the liquid crystal while static electricity remains, there is a concern that the orientation of the liquid crystal molecules may be lost or the panel may be damaged. Furthermore, the presence of static electricity may attract dust or reduce workability.
[0005] To prevent static electricity, antistatic treatment is applied to the substrate of a surface protection film. For example, in a surface protection film having a release layer, a base film layer, and an acrylic adhesive layer in this order, it has been reported that an antistatic layer is formed between the release layer and the base film layer or between the base film layer and the acrylic adhesive layer (Patent Document 2). Also, a removable protective adhesive film has been reported that has an antistatic layer on one side of a transparent resin film and a removable adhesive layer on the antistatic layer (Patent Document 3).
[0006] However, the surface protection film described in Patent Document 2 cannot be said to have sufficiently excellent antistatic properties required for a surface protection film to be attached to high-performance optical or electronic components, nor can it be said to have sufficiently excellent easy releasability, so there is room for improvement.Furthermore, the removable protective adhesive film described in Patent Document 3 cannot be said to have sufficiently excellent antistatic properties required for a surface protection film to be attached to high-performance optical or electronic components.
[0007] To prevent static electricity, a technique has been reported in which the pressure-sensitive adhesive layer constituting the surface protection film itself is imparted with antistatic properties. Specifically, a method has been performed in which an ionic compound, such as an alkali metal salt or an ionic liquid, which functions as an antistatic agent, is incorporated into the pressure-sensitive adhesive layer and then transferred to the adherend (Patent Document 4). However, even the surface protection film described in Patent Document 4 still has room for improvement in order to achieve sufficiently excellent antistatic properties. Furthermore, in the surface protection film described in Patent Document 4, the level of antistatic properties is largely dependent on the amount of antistatic agent in the pressure-sensitive adhesive layer. Therefore, if the amount of antistatic agent is increased in order to achieve excellent antistatic properties, the adherend will be contaminated, and there is a risk of process defects such as peeling occurring when a new component is attached to the adherend after the surface protection film has been peeled off. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent No. 6613516 [Patent Document 2] Patent No. 4170102 [Patent Document 3] International Publication No. 2013 / 129303 Brochure [Patent Document 4] Patent No. 6896927 Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a surface protection film that is attached to exposed surfaces of optical or electronic components to prevent the surfaces of the optical or electronic components from being scratched during processing, assembly, inspection, transportation, etc. in the manufacturing process of the optical or electronic components, and that exhibits both excellent easy releasability and excellent antistatic properties. Another object of the present invention is to provide optical or electronic components to which such a surface protection film is attached. [Means for solving the problem]
[0010] [1] A surface protection film according to an embodiment of the present invention is a surface protection film having a substrate layer, an antistatic layer, and an adhesive layer in this order, wherein the antistatic layer contains a binder resin and a conductive polymer, and the adhesive constituting the adhesive layer is formed from an adhesive composition, the adhesive composition contains a base polymer and a fluorine-based compound, and the base polymer is a urethane prepolymer. [2] In the surface protective film according to the above item [1], the pressure-sensitive adhesive composition may contain a fatty acid ester. [3] In the surface protective film according to the above item [2], the fatty acid ester may have a molecular weight of 300 to 400. [4] In the surface protective film according to any one of [1] to [3] above, the pressure-sensitive adhesive composition may contain an ionic compound. [5] In the surface protection film according to any one of [1] to [4] above, the amount of residual sulfur on the surface of the acrylic plate may be less than 0.1 atomic % after the pressure-sensitive adhesive layer side of the surface protection film is attached to the surface of an acrylic plate, left at 23°C for 30 minutes, and then the surface protection film is peeled off from the surface of the acrylic plate. [6] In the surface protective film according to the above [4] or [5], the content of the ionic compound may be 0.4 parts by weight to 3.0 parts by weight per 100 parts by weight of the base polymer. [7] In the surface protective film according to any one of the above [4] to [6], the ionic compound may have a molecular weight of 200 to 350. [8] In the surface protection film according to any one of [1] to [7] above, the pressure-sensitive adhesive composition may contain a polyfunctional isocyanate compound, and the equivalent ratio of the NCO groups of the polyfunctional isocyanate compound to the OH groups of the polyol may be 1.6 to 2.5, expressed as NCO groups / OH groups. [9] The surface protection film according to any one of [1] to [8] above, wherein the surface free energy of the surface of the pressure-sensitive adhesive layer with respect to diiodomethane is 3.5 mJ / m 2 ~7.0mJ / m 2 may be.
[10] In the surface protective film according to any one of [1] to [9] above, the content of the fluorine-based compound may be 0.1 to 3.0 parts by weight per 100 parts by weight of the base polymer.
[11] An optical member according to an embodiment of the present invention has the surface protection film according to any one of [1] to
[10] above attached thereto.
[12] An electronic device according to an embodiment of the present invention has attached thereto a surface protection film according to any one of [1] to
[10] above. [Effects of the Invention]
[0011] According to the present invention, there can be provided a surface protection film that is attached to exposed surfaces of optical or electronic components in the manufacturing process of the optical or electronic components to prevent the surfaces of the optical or electronic components from being scratched during processing, assembly, inspection, transportation, etc., and that exhibits both excellent easy releasability and excellent antistatic properties. Furthermore, there can be provided an optical or electronic component to which such a surface protection film is attached. [Brief explanation of the drawings]
[0012] [Figure 1] 1 is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0013] When the expression "weight" appears in this specification, it may be read as "mass," which is a commonly used SI unit indicating weight.
[0014] In this specification, the term "(meth)acrylic" means "acrylic and / or methacrylic", the term "(meth)acrylate" means "acrylate and / or methacrylate", the term "(meth)allyl" means "allyl and / or methallyl", and the term "(meth)acrolein" means "acrolein and / or methacrolein". <<A. Surface protection film>> The surface protection film according to the embodiment of the present invention has a substrate layer, an antistatic layer, and a pressure-sensitive adhesive layer in this order.
[0015] The surface protection film according to an embodiment of the present invention may include any appropriate other members or layers as long as the surface protection film has a substrate layer, an antistatic layer, and a pressure-sensitive adhesive layer in this order, as long as the effects of the present invention are not impaired. Examples of such other members or layers include any appropriate other members or layers as long as the effects of the present invention are not impaired. Examples of such other members or layers include a release liner.
[0016] Fig. 1 is a schematic cross-sectional view of a surface protection film according to one embodiment of the present invention. In Fig. 1, a surface protection film 10 comprises a substrate layer 1, an antistatic layer 2, and an adhesive layer 3. In the embodiment shown in Fig. 1, the substrate layer 1, the antistatic layer 2, and the adhesive layer 3 are directly laminated together.
[0017] 1, any appropriate release liner (sometimes referred to as a release sheet or separator) may be provided (not shown) on the surface of the pressure-sensitive adhesive layer 3 opposite the antistatic layer 2 for protection until use, etc. Examples of release liners include release liners in which the surface of a substrate (liner substrate) such as paper or plastic film is treated with silicone, and release liners in which the surface of a substrate (liner substrate) such as paper or plastic film is laminated with a polyolefin resin.
[0018] Examples of plastic films that can be used as liner substrates include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polybutylene terephthalate films, polyurethane films, and ethylene-vinyl acetate copolymer films.
[0019] The thickness of the release liner is preferably 1 μm to 500 μm, more preferably 3 μm to 450 μm, even more preferably 5 μm to 400 μm, and particularly preferably 10 μm to 300 μm.
[0020] The thickness of the surface protection film according to the embodiment of the present invention is preferably 5 μm to 500 μm, more preferably 10 μm to 450 μm, even more preferably 15 μm to 400 μm, and particularly preferably 20 μm to 300 μm.
[0021] The surface protection film according to an embodiment of the present invention has its pressure-sensitive adhesive layer attached to the surface of an acrylic plate, left at 23°C for 30 minutes, and then peeled from the acrylic plate surface at a peel angle of 180° and a peel rate of 300 mm / min at 23°C. The peel force A is preferably 3.0 gf / 25 mm or less, more preferably 2.5 gf / 25 mm or less, even more preferably 2.3 gf / 25 mm or less, even more preferably 2.0 gf / 25 mm or less, particularly preferably 1.8 gf / 25 mm or less, and most preferably 1.6 gf / 25 mm or less. If the peel force A is within the above range, the surface protection film according to an embodiment of the present invention can exhibit excellent easy releasability. To prevent unintended peeling during the manufacturing process, the lower limit of the peel force A is preferably 0.5 gf / 25 mm or more. The method for measuring the peel force A will be described later.
[0022] The surface protection film according to an embodiment of the present invention has its pressure-sensitive adhesive layer attached to the surface of an acrylic plate, left at 50°C for one day, and then peeled from the acrylic plate surface at 23°C at a peel angle of 180° and a peel rate of 300 mm / min. The peel force B is preferably 10.0 gf / 25 mm or less, more preferably 8.0 gf / 25 mm or less, even more preferably 6.0 gf / 25 mm or less, even more preferably 5.5 gf / 25 mm or less, particularly preferably 5.0 gf / 25 mm or less, and most preferably 4.5 gf / 25 mm or less. When the peel force B is within the above range, the surface protection film according to an embodiment of the present invention can exhibit excellent easy releasability while maintaining stability of the peel force over time. To prevent unintended peeling during the manufacturing process, the lower limit of the peel force B is preferably 0.5 gf / 25 mm or more. The method for measuring the peel force B will be described later.
[0023] In the surface protection film according to the embodiment of the present invention, the rate of increase in peel strength over time from the peel strength A to the peel strength B (rate of increase in peel strength over time (%) = (peel strength B / peel strength A) × 100 (%)) is preferably 390% or less, more preferably 350% or less, even more preferably 330% or less, particularly preferably 310% or less, and most preferably 300% or less. The lower limit of the rate of increase in peel strength over time is preferably as small as possible, and is preferably 100% or more. When the rate of increase in peel strength over time is within the above range, the surface protection film according to the embodiment of the present invention can better exhibit stability of the peel strength over time.
[0024] In a surface protection film according to an embodiment of the present invention, after the pressure-sensitive adhesive layer side of the film is attached to the surface of an acrylic plate, left at 23°C for 30 minutes, and then the surface protection film is peeled off from the surface of the acrylic plate, the amount of residual sulfur on the surface of the acrylic plate is preferably less than 0.1 atomic %. The lower limit of the residual sulfur amount is preferably as small as possible, and is preferably 0 atomic % or greater. When the residual sulfur amount is within the above range, the surface protection film according to an embodiment of the present invention can suppress contamination of the adherend after being attached to the adherend and peeled off, thereby preventing process defects such as peeling when a new component is attached to the adherend. The residual sulfur amount serves as an indicator of the extent to which the pressure-sensitive adhesive component of the surface protection film has transferred to the surface of the adherend and contaminated it. The smaller the residual sulfur amount, the less contaminated the adherend the surface protection film is, and the larger the residual sulfur amount, the more contaminated the adherend the surface protection film is. A method for measuring the residual sulfur amount will be described later.
[0025] The surface protection film according to an embodiment of the present invention is stuck with its adhesive layer side to the surface of an acrylic plate, left to stand at 23°C for one day, and then peeled from the surface of the acrylic plate at a peel angle of 180° and a peel speed of 300 mm / min. Then, adhesive tape ("No. 31B" manufactured by Nitto Denko Corporation, 19 mm wide and cut to a length of 150 mm, substrate thickness = 25 μm) is stuck to the surface of the acrylic plate, left to stand at a temperature of 23°C for 30 minutes, and then the adhesive strength when the adhesive tape is peeled from the surface of the acrylic plate at a peel angle of 180° and a peel speed of 300 mm / min at a temperature of 23°C is measured. is defined as adhesive strength C, and the adhesive strength when the adhesive tape is attached to the surface of an acrylic plate that has not been subjected to the release treatment, left at a temperature of 23°C for 30 minutes, and then peeled from the acrylic plate surface at a peel angle of 180° and a peel rate of 300 mm / min at a temperature of 23°C is defined as adhesive strength D. The residual adhesive strength to acrylic plate (%) = (adhesive strength C / adhesive strength D) × 100(%) is preferably 80% or more, more preferably 85% or more, even more preferably 90% or more, particularly preferably 92% or more, and most preferably 95% or more. The upper limit of the residual adhesive strength to acrylic plate is preferably as high as possible, and is preferably 100% or less. When the residual adhesive strength to acrylic plate is within the above range, contamination of the adherend after attachment to the adherend and peeling can be suppressed in the surface protective film according to an embodiment of the present invention, and process defects such as peeling can be suppressed when a new member is attached to the adherend. The residual adhesion rate to acrylic plate serves as an index of the degree to which the adhesive component of the surface protection film has been transferred to the surface of the adherend and contaminated. The larger the value of the residual adhesion rate to acrylic plate, the less contaminated the adherend is with the surface protection film, and the smaller the value of the residual adhesion rate to acrylic plate, the more contaminated the adherend is with the surface protection film. The method for measuring the residual adhesion rate to acrylic plate will be described later.
[0026] The surface protection film according to an embodiment of the present invention has an acrylic peeling electrification voltage of preferably 6.0 kV or less, more preferably 4.0 kV or less, even more preferably 3.0 kV or less, even more preferably 2.5 kV or less, particularly preferably 2.0 kV or less, and most preferably 1.5 kV or less, at a temperature of 23°C and a humidity of 50% RH. The lower limit of the acrylic peeling electrification voltage is preferably as small as possible, but in reality, it is preferably 0.01 kV or more. If the acrylic peeling electrification voltage is within the above range, the surface protection film according to an embodiment of the present invention can exhibit excellent antistatic properties. A method for measuring the acrylic peeling electrification voltage will be described later.
[0027] The surface protection film according to the embodiment of the present invention preferably has a surface resistance value on the pressure-sensitive adhesive layer side of 1.0×10 at a temperature of 23° C. and a humidity of 50% RH. 10 Ω or less, and more preferably 1.0×10 9 Ω or less, and more preferably 5.0×10 8 Ω or less, and particularly preferably 1.0 × 10 8 Ω or less, most preferably 8.0×10 7 The lower limit of the surface resistance is preferably as small as possible, but in reality, it is preferably 1.0×10 4 Ω or more. If the surface resistance value is within the above range, the surface protection film according to the embodiment of the present invention can exhibit excellent antistatic properties. The method for measuring the surface resistance value will be described later.
[0028] ≪A-1. Base material layer≫ The base material layer may be a single layer or may be two or more layers. The base material layer may be stretched.
[0029] The thickness of the base layer is preferably 4 μm to 450 μm, more preferably 8 μm to 400 μm, still more preferably 12 μm to 350 μm, and particularly preferably 16 μm to 250 μm.
[0030] For the surface of the base layer on which the pressure-sensitive adhesive layer is not applied, a release treatment can be performed by adding a fatty acid amide, polyethyleneimine, a long-chain alkyl additive, or the like to the base layer, or a coating layer made of any appropriate release agent such as a silicone-based, long-chain alkyl-based, or fluorine-based release agent can be provided, for example, in order to form a roll that is easy to unwind.
[0031] Any appropriate material can be used as the material for the substrate layer depending on the application. Examples include plastic, paper, metal film, nonwoven fabric, etc. Plastic is preferred. That is, the substrate layer is preferably a plastic film. The substrate layer may be made of one material or two or more materials. For example, it may be made of two or more plastics.
[0032] Examples of the plastics include polyester resins, polyamide resins, and polyolefin resins. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Examples of polyolefin resins include homopolymers of olefin monomers and copolymers of olefin monomers. Specific examples of polyolefin resins include homopolypropylene; propylene copolymers such as block copolymers, random copolymers, and graft copolymers containing ethylene as a copolymerization component; reactor TPO; ethylene polymers such as low-density, high-density, linear low-density, and ultra-low-density copolymers; and ethylene copolymers such as ethylene-propylene copolymers, ethylene-vinyl acetate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, ethylene-butyl acrylate copolymers, ethylene-methacrylic acid copolymers, and ethylene-methyl methacrylate copolymers.
[0033] The substrate layer may contain any appropriate additives as needed. Examples of additives that may be contained in the substrate layer include antioxidants, ultraviolet absorbers, light stabilizers, antistatic agents, fillers, pigments, surfactants, inorganic salts, polyhydric alcohols, and metal compounds. The type, number, and amount of additives that may be contained in the substrate layer may be appropriately set depending on the purpose. Note that a substrate layer containing an antistatic agent as an additive is considered to be different from the antistatic layer in the present invention.
[0034] <A-2. Antistatic layer> The antistatic layer may be disposed at least between the substrate layer and the pressure-sensitive adhesive layer. The antistatic layer may be provided on the substrate layer on the opposite side to the pressure-sensitive adhesive layer.
[0035] The antistatic layer may be a single layer or may be two or more layers.
[0036] The thickness of the antistatic layer may be any appropriate thickness depending on the purpose, as long as it does not impair the effects of the present invention. In order to further exhibit the effects of the present invention, the thickness of the antistatic layer is preferably 3 nm to 100 nm, more preferably 5 nm to 80 nm, even more preferably 8 nm to 60 nm, and particularly preferably 10 nm to 50 nm.
[0037] The antistatic layer includes a binder resin and a conductive polymer. The surface protection film according to the embodiment of the present invention can exhibit excellent antistatic properties by including a binder resin and a conductive polymer in the antistatic layer disposed between the substrate layer and the pressure-sensitive adhesive layer.
[0038] The binder resin in the antistatic layer may be of only one kind or may be of two or more kinds, and the conductive polymer in the antistatic layer may be of only one kind or may be of two or more kinds.
[0039] The antistatic layer may contain any other appropriate components as long as the effects of the present invention are not impaired.
[0040] The content of the binder resin in the antistatic layer, in terms of solid content, is preferably 50 to 100 parts by weight, more preferably 70 to 100 parts by weight, even more preferably 90 to 100 parts by weight, and particularly preferably 95 to 100 parts by weight.
[0041] The content of the conductive polymer in the antistatic layer, as a solid content ratio, is preferably 3 to 40 parts by weight, more preferably 5 to 35 parts by weight, even more preferably 8 to 32 parts by weight, and particularly preferably 10 to 30 parts by weight, relative to 100 parts by weight of the binder resin.
[0042] The binder resin preferably contains a polyester resin, which can further enhance the effects of the present invention. The content of the polyester resin in the binder resin, in terms of solid content, is preferably 50% by weight to 100% by weight, more preferably 70% by weight to 100% by weight, even more preferably 90% by weight to 100% by weight, particularly preferably 95% by weight to 100% by weight, and most preferably substantially 100% by weight.
[0043] The binder resin may contain a resin other than a polyester resin, such as at least one resin selected from the group consisting of an acrylic resin, an acrylic urethane resin, an acrylic styrene resin, an acrylic silicone resin, a silicone resin, a polysilazane resin, a polyurethane resin, a fluororesin, and a polyolefin resin.
[0044] The antistatic layer is preferably formed by coating a conductive coating liquid containing a binder resin and a conductive polymer on any suitable substrate layer, as this can further enhance the effects of the present invention. Specifically, for example, the antistatic layer is formed by coating a conductive coating liquid containing a binder resin and a conductive polymer on a substrate layer. After coating, the coating is dried as needed, and a curing treatment (heat treatment, ultraviolet treatment, etc.) is performed as needed. Any appropriate coating method can be used as long as it does not impair the effects of the present invention. Examples of such coating methods include roll coating, gravure roll coating, reverse roll coating, kiss roll coating, dip roll coating, bar coating, roll brush coating, spray coating, knife coating, air knife coating, comma coating, direct coating, and die coating.
[0045] The conductive coating liquid preferably contains a binder resin, a conductive polymer, a crosslinking agent, and a solvent, and more preferably contains a polyester resin, a conductive polymer, a crosslinking agent, and a solvent, in order to more effectively exhibit the effects of the present invention.
[0046] The polyester resin preferably contains polyester as a main component, and the content of polyester in the polyester resin is preferably more than 50% by weight, more preferably 75% by weight or more, even more preferably 90% by weight or more, and particularly preferably substantially 100% by weight.
[0047] As the polyester, any appropriate polyester can be used as long as it does not impair the effects of the present invention. Preferably, such polyester has a structure obtained by condensing one or more compounds (polycarboxylic acid components) selected from polycarboxylic acids (e.g., dicarboxylic acid compounds) having two or more carboxyl groups in one molecule and derivatives thereof (e.g., anhydrides, esters, halides, etc. of polycarboxylic acids) with one or more compounds (polyhydric alcohol components) selected from polyhydric alcohols (e.g., diols) having two or more hydroxyl groups in one molecule.
[0048] As the polycarboxylic acid component, any appropriate polycarboxylic acid can be used as long as it does not impair the effects of the present invention. Examples of such polycarboxylic acids include oxalic acid, malonic acid, difluoromalonic acid, alkylmalonic acid, succinic acid, tetrafluorosuccinic acid, alkylsuccinic acid, (±)-malic acid, meso-tartaric acid, itaconic acid, maleic acid, methylmaleic acid, fumaric acid, methylfumaric acid, acetylenedicarboxylic acid, glutaric acid, hexafluoroglutaric acid, methylglutaric acid, glutaconic acid, adipic acid, dithioadipic acid, methyladipic acid, dimethyladipic acid, tetramethyladipic acid, methyleneadipic acid, muconic acid, galactaric acid, pimelic acid, suberic acid, Aliphatic dicarboxylic acids such as perfluorosuberic acid, 3,3,6,6-tetramethylsuberic acid, azelaic acid, sebacic acid, perfluorosebacic acid, brassylic acid, dodecyldicarboxylic acid, tridecyldicarboxylic acid, and tetradecyldicarboxylic acid; alicyclic dicarboxylic acids such as cycloalkyldicarboxylic acids (e.g., 1,4-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid), 1,4-(2-norbornene)dicarboxylic acid, 5-norbornene-2,3-dicarboxylic acid (himic acid), adamantanedicarboxylic acid, and spiroheptanedicarboxylic acid;Phthalic acid, isophthalic acid, dithioisophthalic acid, methylisophthalic acid, dimethylisophthalic acid, chloroisophthalic acid, dichloroisophthalic acid, terephthalic acid, methyl terephthalic acid, dimethyl terephthalic acid, chloroterephthalic acid, bromoterephthalic acid, naphthalenedicarboxylic acid, oxofluorenedicarboxylic acid, anthracene dicarboxylic acid, biphenyl dicarboxylic acid, biphenylenedicarboxylic acid, dimethylbiphenylenedicarboxylic acid, 4,4"-p-terephenylenedicarboxylic acid, 4,4"-p-quarelphenyldicarboxylic acid, bibenzyl dicarboxylic acid, azobenzenedicarboxylic acid, homophthalic acid, phenylene diacetic acid, phenyl Examples of suitable polycarboxylic acids include aromatic dicarboxylic acids such as dipropionic acid, naphthalenedicarboxylic acid, naphthalenedipropionic acid, biphenyldiacetic acid, biphenyldipropionic acid, 3,3'-[4,4'-(methylenedi-p-biphenylene)]dipropionic acid, 4,4'-bibenzyldiacetic acid, 3,3'(4,4'-bibenzyl)dipropionic acid, and oxydi-p-phenylenediacetic acid; acid anhydrides of any of the above polycarboxylic acids; esters of any of the above polycarboxylic acids (e.g., alkyl esters, monoesters, diesters, etc.); and acid halides corresponding to any of the above polycarboxylic acids (e.g., dicarboxylic acid chlorides).
[0049] Preferred examples of the polycarboxylic acid component include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid, and their acid anhydrides; aliphatic dicarboxylic acids such as adipic acid, sebacic acid, azelaic acid, succinic acid, fumaric acid, maleic acid, himic acid, and 1,4-cyclohexanedicarboxylic acid, and their acid anhydrides; and lower alkyl esters of these dicarboxylic acids (for example, esters with monoalcohols having 1 to 3 carbon atoms).
[0050] As the polyhydric alcohol component, any suitable polyhydric alcohol can be used as long as it does not impair the effects of the present invention. Examples of such polyhydric alcohols include diols such as ethylene glycol, propylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 3-methylpentanediol, diethylene glycol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, xylylene glycol, hydrogenated bisphenol A, and bisphenol A; and alkylene oxide adducts of these diols (e.g., ethylene oxide adducts, propylene oxide adducts, etc.).
[0051] The number average molecular weight of the polyester resin is preferably 3,000 to 100,000, more preferably 6,000 to 50,000, even more preferably 8,000 to 30,000, and particularly preferably 10,000 to 20,000, in order to further exert the effects of the present invention.
[0052] The glass transition temperature (Tg) of the polyester resin is preferably 0°C to 120°C, more preferably 5°C to 80°C, even more preferably 10°C to 60°C, and particularly preferably 15°C to 40°C, in order to further exhibit the effects of the present invention.
[0053] As the polyester resin, for example, commercially available products under the trade name "Vylonal (registered trademark)" series manufactured by Toyobo Co., Ltd. can be used.
[0054] Any suitable conductive polymer can be used as the conductive polymer as long as it does not impair the effects of the present invention. Examples of such conductive polymers include conductive polymers in which a π-conjugated conductive polymer is doped with a polyanion. Examples of π-conjugated conductive polymers include chain-like conductive polymers such as polythiophene, polypyrrole, polyaniline, and polyacetylene. Examples of polyanions include polystyrene sulfonic acid, polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyacrylic acid ethyl sulfonic acid, and polymethacrylic carboxylic acid.
[0055] Any appropriate crosslinking agent may be used as the crosslinking agent contained in the conductive coating liquid as long as it does not impair the effects of the present invention. The crosslinking agent may be one type or two or more types. Examples of such crosslinking agents include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, melamine-based crosslinking agents, and peroxide-based crosslinking agents, as well as urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, carbodiimide-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, and amine-based crosslinking agents. Among these, melamine-based crosslinking agents are preferred.
[0056] The content of the crosslinking agent in the conductive coating liquid, as a solid content ratio, is preferably 0.5 to 15 parts by weight, more preferably 1 to 12 parts by weight, even more preferably 2 to 9 parts by weight, and particularly preferably 3 to 7 parts by weight, relative to 100 parts by weight of the binder resin.
[0057] Examples of the solvent include organic solvents, water, and mixed solvents thereof. Examples of the organic solvent include esters such as ethyl acetate; ketones such as methyl ethyl ketone, acetone, and cyclohexanone; cyclic ethers such as tetrahydrofuran (THF) and dioxane; aliphatic or alicyclic hydrocarbons such as n-hexane and cyclohexane; aromatic hydrocarbons such as toluene and xylene; aliphatic or alicyclic alcohols such as methanol, ethanol, n-propanol, isopropanol, and cyclohexanol; and glycol ethers such as alkylene glycol monoalkyl ethers (e.g., ethylene glycol monomethyl ether and ethylene glycol monoethyl ether) and dialkylene glycol monoalkyl ethers. The solvent is preferably water or a mixed solvent of water and ethanol.
[0058] The conductive coating liquid may contain any other appropriate components as long as the effects of the present invention are not impaired.
[0059] <A-3. Adhesive layer> The thickness of the pressure-sensitive adhesive layer is preferably 5 μm to 150 μm, more preferably 10 μm to 130 μm, even more preferably 30 μm to 120 μm, particularly preferably 50 μm to 100 μm, and most preferably 60 μm to 90 μm, in order to further exhibit the effects of the present invention.
[0060] The adhesive layer preferably has a surface free energy of 3.5 mJ / m with respect to diiodomethane. 2 ~7.5mJ / m 2 and more preferably 3.5 mJ / m 2 ~7.0mJ / m 2 and more preferably 3.5 mJ / m 2 ~6.5mJ / m 2 and more preferably 3.5 mJ / m 2 ~6.0mJ / m 2 and particularly preferably 3.5 mJ / m 2 ~5.5mJ / m 2 and most preferably 3.7 mJ / m 2 ~5.0mJ / m2 When the surface free energy of the pressure-sensitive adhesive layer with respect to diiodomethane is within the above range, the surface protection film according to the embodiment of the present invention can sufficiently suppress peel electrification voltage and exhibit excellent antistatic properties. When the surface free energy of the pressure-sensitive adhesive layer with respect to diiodomethane is too low outside the above range, the peel electrification voltage cannot be sufficiently suppressed and excellent antistatic properties may not be exhibited. When the surface free energy of the pressure-sensitive adhesive layer with respect to diiodomethane is too high outside the above range, the adherend may be contaminated.
[0061] The surface free energy of the adhesive layer with respect to diiodomethane can be easily measured, as described below. By designing the adhesive layer so that this surface free energy falls within the above-mentioned specified range, the surface protection film according to an embodiment of the present invention can sufficiently suppress the peeling electrification voltage and exhibit excellent antistatic properties.
[0062] The pressure-sensitive adhesive layer is composed of a pressure-sensitive adhesive. The pressure-sensitive adhesive is formed from a pressure-sensitive adhesive composition. That is, the pressure-sensitive adhesive formed from the pressure-sensitive adhesive composition forms a layer, thereby becoming the pressure-sensitive adhesive layer.
[0063] An adhesive can be defined as something formed from an adhesive composition. This is because an adhesive becomes an adhesive when an adhesive composition undergoes a crosslinking reaction due to heating or ultraviolet irradiation, etc., making it impossible and impractical to directly identify an adhesive by its structure ("impossible or impractical circumstances"). Therefore, the definition of "something formed from an adhesive composition" appropriately identifies an adhesive as a "product."
[0064] The pressure-sensitive adhesive layer can be formed by any appropriate method. Examples of such methods include a method in which a pressure-sensitive adhesive composition is applied to any appropriate substrate, heated and dried as necessary, and cured as necessary to form a pressure-sensitive adhesive layer on the substrate. Examples of such application methods include methods using a gravure roll coater, reverse roll coater, kiss roll coater, dip roll coater, bar coater, knife coater, air knife coater, spray coater, comma coater, direct coater, roll brush coater, etc.
[0065] The pressure-sensitive adhesive composition includes a base polymer and a fluorine-based compound, and the base polymer is a urethane prepolymer. Since the pressure-sensitive adhesive composition includes a base polymer and a fluorine-based compound, and the base polymer is a urethane prepolymer, the surface protection film according to the embodiment of the present invention can exhibit excellent antistatic properties by sufficiently suppressing peel electrification voltage.
[0066] In the present invention, the effects of the present invention can be achieved by the PSA composition containing a fluorine-based compound in addition to the base polymer.
[0067] The content of the base polymer in the pressure-sensitive adhesive composition, calculated as solid content, is preferably 60% by weight to 99.9% by weight, more preferably 65% by weight to 99.9% by weight, even more preferably 70% by weight to 99.9% by weight, particularly preferably 75% by weight to 99.9% by weight, and most preferably 80% by weight to 99.9% by weight. When the content of the base polymer in the pressure-sensitive adhesive composition, calculated as solid content, is within the above range, the surface protection film according to the embodiment of the present invention can exhibit more sufficient suppression of peel electrification voltage and more excellent antistatic properties.
[0068] The content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is preferably 0.01 to 3.0 parts by weight, more preferably 0.1 to 3.0 parts by weight, even more preferably 0.2 to 2.0 parts by weight, particularly preferably 0.2 to 1.5 parts by weight, and most preferably 0.2 to 1.0 parts by weight. When the content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is within the above range, the surface protection film according to the embodiment of the present invention can more sufficiently suppress peel electrification voltage and exhibit better antistatic properties. If the content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is too low outside the above range, the peel electrification voltage may not be sufficiently suppressed, and excellent antistatic properties may not be exhibited. If the content ratio of the fluorine-based compound relative to 100 parts by weight of the base polymer is too high outside the above range, the adherend may be contaminated.
[0069] <A-3-a.ベースポリマー> The urethane prepolymer, which is the base polymer, can react with a polyfunctional isocyanate compound to form a urethane resin. More specifically, the urethane resin is preferably formed from a composition containing the urethane prepolymer and the polyfunctional isocyanate compound, and more specifically, the urethane resin is formed by curing the composition containing the urethane prepolymer and the polyfunctional isocyanate compound. As a method for forming the urethane resin by curing the composition containing the urethane prepolymer and the polyfunctional isocyanate compound, any appropriate method can be used as long as it does not impair the effects of the present invention, such as a urethanization reaction method using bulk polymerization or solution polymerization.
[0070] There are two methods for producing urethane resins: the "one-shot method," in which a urethane adhesive is produced by directly reacting a polyol with a polyfunctional isocyanate without using a urethane prepolymer, and the "prepolymer method," in which a urethane adhesive is produced by reacting a urethane prepolymer with a polyfunctional isocyanate. In the present invention, the urethane prepolymer used as the base polymer refers to the urethane prepolymer that is reacted with the polyfunctional isocyanate in the "prepolymer method," and is different from the polyol that is reacted with the polyfunctional isocyanate in the "one-shot method."
[0071] The urethane prepolymer may be of one type only, or of two or more types.
[0072] The number average molecular weight Mn of the urethane prepolymer is preferably 3,000 to 1,000,000.
[0073] A urethane prepolymer is typically a polymer obtained by reacting a polyol with a polyfunctional isocyanate compound, and has an isocyanate group at the molecular terminal.
[0074] The urethane prepolymer is preferably a polyurethane polyol, and more preferably is obtained by reacting at least one selected from a polyester polyol (a1) and a polyether polyol (a2) with a polyfunctional isocyanate compound in the presence or absence of a catalyst.
[0075] The polyester polyol (a1) may be of one kind or two or more kinds.
[0076] The polyether polyol (a2) may be one kind or two or more kinds.
[0077] Any suitable polyester polyol can be used as the polyester polyol (a1). Examples of such polyester polyols (a1) include polyester polyols obtained by reacting an acid component with a glycol component. Examples of the acid component include terephthalic acid, adipic acid, azelaic acid, sebacic acid, phthalic anhydride, isophthalic acid, and trimellitic acid. Examples of the glycol component include ethylene glycol, propylene glycol, diethylene glycol, butylene glycol, 1,6-hexane glycol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, polyoxyethylene glycol, polyoxypropylene glycol, 1,4-butanediol, neopentyl glycol, butylethylpentanediol, glycerin, trimethylolpropane, and pentaerythritol. In addition to these, examples of the polyester polyol (a1) include polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, poly(β-methyl-γ-valerolactone), and polyvalerolactone.
[0078] The molecular weight of the polyester polyol (a1) can range from low to high. The molecular weight of the polyester polyol (a1) is preferably a number average molecular weight Mn of 100 to 100,000. If the number average molecular weight Mn is less than 100, the reactivity may be high and gelation may occur easily. If the number average molecular weight Mn exceeds 100,000, the reactivity may be low and the cohesive force of the polyurethane polyol itself may be reduced. The amount of polyester polyol (a1) used is preferably 0 mol % to 90 mol % of the polyols constituting the polyurethane polyol.
[0079] Any suitable polyether polyol can be used as the polyether polyol (a2). Examples of such polyether polyol (a2) include polyether polyols obtained by polymerizing oxirane compounds such as ethylene oxide, propylene oxide, butylene oxide, and tetrahydrofuran using a low-molecular-weight polyol such as water, propylene glycol, ethylene glycol, glycerin, or trimethylolpropane as an initiator. Specific examples of such polyether polyol (a2) include polyether polyols having two or more functional groups, such as polypropylene glycol, polyethylene glycol, and polytetramethylene glycol.
[0080] The molecular weight of the polyether polyol (a2) can range from low to high. The molecular weight of the polyether polyol (a2) is preferably a number average molecular weight Mn of 100 to 100,000. If the number average molecular weight Mn is less than 100, the reactivity may be high and gelation may occur easily. If the number average molecular weight Mn exceeds 100,000, the reactivity may be low and the cohesive force of the polyurethane polyol itself may be reduced. The amount of polyether polyol (a2) used is preferably 0 mol % to 90 mol % of the polyols constituting the polyurethane polyol.
[0081] If necessary, the polyether polyol (a2) can be used in combination by replacing a part thereof with glycols such as ethylene glycol, 1,4-butanediol, neopentyl glycol, butylethylpentanediol, glycerin, trimethylolpropane, and pentaerythritol, or polyvalent amines such as ethylenediamine, N-aminoethylethanolamine, isophoronediamine, and xylylenediamine.
[0082] The polyether polyol (a2) may be a bifunctional polyether polyol alone, or may be a polyether polyol having a number-average molecular weight Mn of 100 to 100,000 and at least three hydroxyl groups per molecule. When the polyether polyol (a2) is a polyether polyol having a number-average molecular weight Mn of 100 to 100,000 and at least three hydroxyl groups per molecule, the balance between adhesive strength and removability can be improved. If the number-average molecular weight Mn of such a polyether polyol is less than 100, the reactivity may be high and gelation may occur easily. If the number-average molecular weight Mn of such a polyether polyol exceeds 100,000, the reactivity may decrease and the cohesive strength of the polyurethane polyol itself may become weak. The number-average molecular weight Mn of such a polyether polyol is more preferably 100 to 10,000.
[0083] The polyfunctional isocyanate compound that can be reacted with the polyol to obtain the urethane prepolymer may be one type only, or two or more types.
[0084] The polyfunctional isocyanate compound may be any suitable polyfunctional isocyanate compound that can be used in a urethanization reaction, such as a polyfunctional aliphatic isocyanate compound, a polyfunctional alicyclic isocyanate compound, a polyfunctional aromatic isocyanate compound, or a polyfunctional aromatic-aliphatic isocyanate compound.
[0085] Examples of polyfunctional aliphatic isocyanate compounds include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, 2,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.
[0086] Examples of polyfunctional alicyclic isocyanate compounds include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate, 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,4-bis(isocyanatemethyl)cyclohexane, 1,4-bis(isocyanatemethyl)cyclohexane, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.
[0087] Examples of polyfunctional aromatic diisocyanate compounds include 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, 4,4',4"-triphenylmethane triisocyanate, dianisidine diisocyanate, and xylylene diisocyanate.
[0088] Examples of polyfunctional aromatic aliphatic isocyanate compounds include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.
[0089] Examples of the polyfunctional isocyanate compound include trimethylolpropane adducts of the above-mentioned various polyfunctional isocyanate compounds, biuret compounds obtained by reacting with water, and trimers having an isocyanurate ring. These compounds may also be used in combination.
[0090] The isocyanate groups of the polyfunctional isocyanate compound are preferably used in a molar ratio such that they are in excess of the hydroxyl groups of the polyol. The equivalent ratio of NCO groups to OH groups, expressed as NCO groups / OH groups, in the polyol and polyfunctional isocyanate compound that can be used to obtain a urethane prepolymer is preferably 1.01 to 5.0, more preferably 1.1 to 3.0, even more preferably 1.1 to 2.0, particularly preferably 1.1 to 1.8, and most preferably 1.2 to 1.6.
[0091] Any suitable catalyst can be used to obtain the urethane prepolymer, such as a tertiary amine compound or an organometallic compound.
[0092] Examples of tertiary amine compounds include triethylamine, triethylenediamine, and 1,8-diazabicyclo(5,4,0)-undecene-7 (DBU).
[0093] Examples of organometallic compounds include tin compounds, non-tin compounds, etc. Examples of tin compounds include dibutyltin dichloride, dibutyltin oxide, dibutyltin dibromide, dibutyltin dimaleate, dibutyltin dilaurate (DBTDL), dibutyltin diacetate, dibutyltin sulfide, tributyltin sulfide, tributyltin oxide, tributyltin acetate, triethyltin ethoxide, tributyltin ethoxide, dioctyltin oxide, tributyltin chloride, tributyltin trichloroacetate, and tin 2-ethylhexanoate. Examples of non-tin compounds include titanium compounds such as dibutyltitanium dichloride, tetrabutyltitanium, and butoxytitanium trichloride; lead compounds such as lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate; iron compounds such as iron 2-ethylhexanoate and iron acetylacetonate; cobalt compounds such as cobalt benzoate and cobalt 2-ethylhexanoate; zinc compounds such as zinc naphthenate and zinc 2-ethylhexanoate; and zirconium compounds such as zirconium naphthenate.
[0094] When a catalyst is used in preparing the urethane prepolymer, the amount of the catalyst used is preferably 0.001 to 1.0% by weight, more preferably 0.005 to 1.0% by weight, based on the total amount of the polyester polyol (a1), the polyether polyol (a2), and the polyfunctional isocyanate compound.
[0095] When a catalyst is used to prepare a urethane prepolymer, in a system containing two types of polyols, a polyester polyol and a polyether polyol, the difference in reactivity between them can easily lead to problems such as gelation or cloudiness of the reaction solution when a single catalyst is used. Therefore, by using two types of catalysts to obtain the urethane prepolymer, it becomes easier to control the reaction rate, catalyst selectivity, and the like, thereby solving these problems. Examples of such combinations of two types of catalysts include a tertiary amine compound / organometallic compound, a tin compound / non-tin compound, and a tin compound / tin compound. A tin compound / tin compound is preferred, and a combination of dibutyltin dilaurate and tin 2-ethylhexanoate is more preferred. The weight ratio of tin 2-ethylhexanoate / dibutyltin dilaurate is preferably less than 1, more preferably 0.2 to 0.6. A combination ratio of 1 or more can lead to gelation due to the balance of catalytic activity.
[0096] When a catalyst is used in preparing the urethane prepolymer, the reaction temperature is preferably less than 100° C., and more preferably 85 to 95° C. If the temperature is 100° C. or higher, it may become difficult to control the reaction rate and crosslinked structure, and it may become difficult to obtain a urethane prepolymer having the desired molecular weight.
[0097] When preparing the urethane prepolymer, it is not necessary to use a catalyst. In that case, the reaction temperature is preferably 100° C. or higher, more preferably 110° C. or higher. When preparing the urethane prepolymer without a catalyst, it is preferable to carry out the reaction for 3 hours or more.
[0098] Examples of methods for preparing urethane prepolymers include: 1) a method of charging a polyol, a catalyst, and a polyfunctional isocyanate compound into a full-volume flask; and 2) a method of charging a polyol and a catalyst into a flask and adding the polyfunctional isocyanate compound dropwise. In the method of 2), after dropping the polyfunctional isocyanate compound, the polyol and the polyfunctional isocyanate compound may be further added. As a method for preparing urethane prepolymers, the method of 2) is preferable for controlling the reaction.
[0099] When preparing urethane prepolymers, any suitable solvent can be used. Examples of such solvents include methyl ethyl ketone, ethyl acetate, toluene, xylene, and acetone. Among these solvents, toluene is preferably used.
[0100] <A-3-b. Polyfunctional isocyanate compound> The urethane prepolymer as a base polymer reacts with a polyfunctional isocyanate compound to form a urethane resin. Therefore, the adhesive composition preferably contains a polyfunctional isocyanate compound.
[0101] The polyfunctional isocyanate compound may be only one kind or two or more kinds.
[0102] As the polyfunctional isocyanate compound, any suitable polyfunctional isocyanate compound that can be used in the urethanization reaction can be adopted. As such a polyfunctional isocyanate compound, the polyfunctional isocyanate compounds described as those that can react with a polyol to obtain a urethane prepolymer can be adopted. The polyfunctional isocyanate compound that reacts with the urethane prepolymer as a base polymer to form a urethane resin may be the same as or different from the polyfunctional isocyanate compounds described as those that can react with a polyol to obtain a urethane prepolymer.
[0103] The equivalent ratio of the NCO groups of the polyfunctional isocyanate compound to the OH groups of the urethane prepolymer is preferably 1.0 to 2.7, more preferably 1.2 to 2.5, still more preferably 1.4 to 2.3, and particularly preferably 1.5 to 2.2, expressed as NCO groups / OH groups. When the equivalent ratio of NCO groups / OH groups is within the above range, it is difficult to be easily peeled off from the adherend. Typically, during the manufacturing process of optical members and electronic members, peeling is unlikely to occur after being attached to the exposed surface of the optical member or the electronic member, and when peeling is necessary, a surface protection film that can be easily peeled off can be provided. Further, when the equivalent ratio of NCO groups / OH groups is within the above range, it becomes possible to reduce haze.
[0104] The content ratio of the polyfunctional isocyanate compound in the adhesive composition is preferably 1.0 to 30 parts by weight, more preferably 1.5 to 27 parts by weight, still more preferably 2.0 to 25 parts by weight, still more preferably 2.3 to 23 parts by weight, still more preferably 2.3 to 18 parts by weight, particularly preferably from 2.5 to 18 parts by weight, and most preferably 2.5 to 16 parts by weight, based on 100 parts by weight of the urethane prepolymer. When the content ratio of the polyfunctional isocyanate compound is within the above range, it is difficult to be easily peeled off from the adherend. Typically, during the manufacturing process of optical members and electronic members, peeling is unlikely to occur after being attached to the exposed surface of the optical member or the electronic member, and when peeling is necessary, a surface protection film that can be easily peeled off can be provided. Further, when the content ratio of the polyfunctional isocyanate compound is within the above range, it becomes possible to reduce haze.
[0105] <A-3-c. Fluorine-based compound> As the fluorine-based compound, any suitable fluorine-based compound can be adopted as long as the effects of the present invention are not impaired. By including a fluorine-based compound in the adhesive composition in addition to the base polymer, the surface protection film according to the embodiment of the present invention can sufficiently suppress the peeling charging voltage and exhibit excellent antistatic properties.
[0106] The fluorine-based compound may be one kind or two or more kinds.
[0107] In terms of being able to further exert the effects of the present invention, the fluorine-based compound is preferably a fluorine-based oligomer, more preferably an oligomer having a fluorine-containing group and a hydrophilic group and / or a lipophilic group, and even more preferably an oligomer having a fluorine-containing group, a hydrophilic group and a lipophilic group.
[0108] Representative examples of the fluorine-containing group include fluorine-containing alkyl groups (e.g., CF3-, etc.) and / or fluorine-containing alkylene groups (e.g., -CF2-CF2-, etc.). A hydrophilic group is a group having hydrophilicity, and hydrophilicity is translated into English as "hydrophilic" and is a property generally known to those skilled in the art as meaning "having an affinity for water" (see, for example, McGraw-Hill Scientific and Technical Dictionary (Revised 3rd Edition, Nikkan Kogyo Shimbun, Ltd.)). A lipophilic group is a group having lipophilicity, and lipophilicity is translated into English as "lipophilic" and is a property generally known to those skilled in the art as meaning "having an affinity for oil" (see, for example, McGraw-Hill Scientific and Technical Dictionary (Revised 3rd Edition, Nikkan Kogyo Shimbun, Ltd.)).
[0109] In order to further enhance the effects of the present invention, the fluorine-based compound preferably has a surface tension in a 0.1% toluene solution (the surface tension of toluene is 27.9 mN / m) of 19.0 mN / m to 25.9 mN / m, more preferably 22.0 mN / m to 25.7 mN / m, even more preferably 23.0 mN / m to 25.5 mN / m, particularly preferably 23.5 mN / m to 25.3 mN / m, and most preferably 24.0 mN / m to 25.0 mN / m. By employing such a specific fluorine-based compound as the fluorine-based compound, the surface protection film according to the embodiment of the present invention can sufficiently suppress peel electrification voltage and exhibit excellent antistatic properties, and the pressure-sensitive adhesive layer can exhibit excellent anchoring properties.
[0110] A particularly preferred embodiment of the fluorine-based compound is an oligomer containing a fluorine-containing group, a hydrophilic group, and a lipophilic group, and which has a surface tension of 19.0 mN / m to 25.9 mN / m when dissolved in 0.1% toluene (the surface tension of toluene is 27.9 mN / m). The surface tension is preferably 22.0 mN / m to 25.7 mN / m, more preferably 23.0 mN / m to 25.5 mN / m, even more preferably 23.5 mN / m to 25.3 mN / m, and particularly preferably 24.0 mN / m to 25.0 mN / m. By using such a specific fluorine-based compound as the fluorine-based compound, the surface protection film according to the embodiment of the present invention can exhibit more sufficient suppression of peel electrification voltage, exhibit better antistatic properties, and the pressure-sensitive adhesive layer can exhibit better anchoring properties.
[0111] Examples of oligomers having a fluorine-containing group and a hydrophilic group and / or a lipophilic group include the "Megafac series" manufactured by DIC Corporation.
[0112] Among the "Megafac Series" manufactured by DIC Corporation, examples of oligomers containing a fluorine-containing group, a hydrophilic group, and a lipophilic group include: "Megafac F-477" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 26.4 mN / m), "Megafac F-553" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 26.4 mN / m), "Megafac F-555-A" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 20.4 mN / m), "Megafac F-556" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 27.5 mN / m), "Megafac F-559" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 26.1 mN / m), "Megafac F-562" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 24.8 mN / m), "Megafac F-565" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 27.6 mN / m), "Megafac F-568" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 24.7 mN / m), "Megafac F-571" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 24.8 mN / m), Examples include:
[0113] Among the "Megafac Series" manufactured by DIC Corporation, examples of fluorine-based compounds with a surface tension of 19.0 mN / m to 25.9 mN / m when made into a 0.1% toluene solution (the surface tension of toluene is 27.9 mN / m) include: "Megafac F-251" (fluorine-containing and lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 24.9 mN / m), "Megafac F-253" (fluorine-containing and lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 21.9 mN / m), "Megafac F-551-A" (oligomer containing fluorine and lipophilic groups, surface tension of 0.1% toluene solution = 25.6 mN / m), "Megafac F-552" (fluorine-containing and lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 24.9 mN / m), "Megafac F-554" (fluorine-containing and lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 25.5 mN / m), "Megafac F-555-A" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 20.4 mN / m), "Megafac F-560" (fluorine-containing and lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 20.2 mN / m), "Megafac F-561" (a fluorine-containing, lipophilic group-containing oligomer, surface tension of 23 mN / m when dissolved in 0.1% toluene), "Megafac F-562" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 24.8 mN / m), "Megafac F-563" (fluorine-containing and lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 20.2 mN / m), "Megafac F-568" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 24.7 mN / m), "Megafac F-569" (fluorine-containing and lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 19.7 mN / m), "Megafac F-570" (oligomer containing fluorine-containing groups, hydrophilic groups, lipophilic groups, and carboxyl groups, surface tension when dissolved in 0.1% toluene = 22.9 mN / m), "Megafac F-571" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 24.8 mN / m), "Megafac F-576" (a fluorine-containing, lipophilic group-containing oligomer, surface tension of 0.1% toluene solution = 24.8 mN / m), Examples include:
[0114] Among the "Megafac Series" manufactured by DIC Corporation, examples of fluorine-based compounds that are oligomers containing a fluorine-containing group, a hydrophilic group, and a lipophilic group and have a surface tension of 19.0 mN / m to 25.9 mN / m when made into a 0.1% toluene solution (the surface tension of toluene is 27.9 mN / m) include: "Megafac F-555-A" (oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension when dissolved in 0.1% toluene = 20.4 mN / m), "Megafac F-562" (an oligomer containing a fluorine group, a hydrophilic group, and a lipophilic group, surface tension = 24.8 mN / m when made into a 0.1% toluene solution), "Megafac F-568" (an oligomer containing a fluorine group, a hydrophilic group, and a lipophilic group, surface tension = 24.7 mN / m when made into a 0.1% toluene solution), "Megafac F-570" (an oligomer containing a fluorine group, a hydrophilic group, a lipophilic group, and a carboxyl group, surface tension = 22.9 mN / m when made into a 0.1% toluene solution), "Megafac F-571" (an oligomer containing a fluorine group, a hydrophilic group, and a lipophilic group, surface tension = 24.8 mN / m when made into a 0.1% toluene solution), may be mentioned.
[0115] <A-3-d. Ionic Compound> The adhesive composition may contain an ionic compound. The ionic compound preferably can exhibit an antistatic effect. By using the ionic compound in combination with a fluorine-based compound, it is presumed that due to the interaction with the fluorine-based compound, the ionic compound tends to be unevenly distributed on the surface side (the side bonded to the adherend) of the adhesive layer. The surface protection film according to the embodiment of the present invention can more sufficiently suppress the peeling electrostatic voltage and exhibit more excellent antistatic properties, and the adhesive layer can also exhibit more excellent anchoring properties.
[0116] The ionic compound may be only one kind or two or more kinds.
[0117] The content of the ionic compound relative to 100 parts by weight of the base polymer is preferably 0.2 parts by weight or more, more preferably 0.3 to 4.0 parts by weight, even more preferably 0.4 to 3.0 parts by weight, even more preferably 0.4 to 2.0 parts by weight, particularly preferably 0.4 to 1.5 parts by weight, and most preferably 0.4 to 1.0 parts by weight. When the content of the ionic compound relative to 100 parts by weight of the base polymer is within the above range, the surface protection film according to the embodiment of the present invention can more sufficiently suppress peel electrification voltage and exhibit even more excellent antistatic properties. If the content of the ionic compound relative to 100 parts by weight of the base polymer is too low outside the above range, the peel electrification voltage may not be sufficiently suppressed, and excellent antistatic properties may not be exhibited. If the content of the ionic compound relative to 100 parts by weight of the base polymer is too high outside the above range, the adherend may be contaminated.
[0118] As the ionic compound, any appropriate ionic compound can be used as long as it does not impair the effects of the present invention. As such an ionic compound, an ionic liquid is preferred. The ionic liquid refers to a molten salt (ionic compound) that is liquid at 25°C.
[0119] Any appropriate ionic liquid can be used as the ionic liquid as long as it does not impair the effects of the present invention. As such an ionic liquid, an ionic liquid containing a fluoroorganic anion is preferred, and an ionic liquid composed of a fluoroorganic anion and an onium cation is more preferred, in terms of being able to further exhibit the effects of the present invention.
[0120] As the fluoroorganic anion that can constitute the ionic liquid, any appropriate fluoroorganic anion can be used as long as it does not impair the effects of the present invention. Such a fluoroorganic anion may be completely fluorinated (perfluorinated) or partially fluorinated.
[0121] Such fluoroorganic anions are preferably perfluoroalkylsulfonates, bis(fluorosulfonyl)imides, and bis(perfluoroalkanesulfonyl)imides, in that they can further exhibit the effects of the present invention. Specific examples include trifluoromethanesulfonate, pentafluoroethanesulfonate, heptafluoropropanesulfonate, nonafluorobutanesulfonate, bis(fluorosulfonyl)imide, and bis(trifluoromethanesulfonyl)imide.
[0122] As the onium cation that can constitute the ionic liquid, any appropriate onium cation can be adopted as long as it does not impair the effects of the present invention. Examples of such onium cations include pyridinium cation, pyrrolidinium cation, piperidinium cation, cation having a pyrroline skeleton, cation having a pyrrole skeleton, imidazolium cation, tetrahydropyrimidinium cation, dihydropyrimidinium cation, pyrazolium cation, pyrazolinium cation, tetraalkyl (or substituted alkyl) ammonium cation, trialkyl (or substituted alkyl) sulfonium cation, and tetraalkyl (or substituted alkyl) phosphonium cation. In terms of being able to further exhibit the effects of the present invention, the pyridinium cation, pyrrolidinium cation, piperidinium cation, imidazolium cation, pyrazolium cation, pyrazolinium cation, and tetraalkyl (or substituted alkyl) ammonium cation are preferred.
[0123] Examples of pyridinium cations include 1-hexylpyridinium cation, 1-ethyl-3-methylpyridinium cation, 1-butyl-3-methylpyridinium cation, and 1-octyl-4-methylpyridinium cation. Examples of pyrrolidinium cations include 1-methyl-1-propylpyrrolidinium cation. Examples of piperidinium cations include 1-methyl-1-propylpiperidinium cation. Examples of imidazolium cations include 1-ethyl-3-methylimidazolium cation and 1-hexyl-3-methylimidazolium cation. Examples of pyrazolium cations include 1-methylpyrazolium cation, 3-methylpyrazolium cation, 1-ethyl-2-methylpyrazolinium cation, 1-ethyl-2,3,5-trimethylpyrazolium cation, 1-propyl-2,3,5-trimethylpyrazolium cation, and 1-butyl-2,3,5-trimethylpyrazolium cation. Examples of pyrazolinium cations include 1-ethyl-2,3,5-trimethylpyrazolinium cation, 1-propyl-2,3,5-trimethylpyrazolinium cation, and 1-butyl-2,3,5-trimethylpyrazolinium cation. Examples of tetraalkyl (or substituted alkyl) ammonium cations include trimethylpropyl ammonium cation.
[0124] As the ionic liquid, from the viewpoint of further exhibiting the effects of the present invention, preferred are 1-hexylpyridinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylpyridinium trifluoromethanesulfonate, 1-ethyl-3-methylpyridinium pentafluoroethanesulfonate, 1-ethyl-3-methylpyridinium heptafluoropropanesulfonate, 1-ethyl-3-methylpyridinium nonafluorobutanesulfonate, 1-butyl-3-methylpyridinium trifluoromethanesulfonate, 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide, 1-octyl-4-methylpyridinium bis(fluorosulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide, 1-methyl-1-propylpiperidinium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpiperidinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylimidazolium trifluoromethanesulfonate, 1-ethyl-3-methylimidazolium heptafluoropropanesulfonate, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-hexyl-3-methylimidazolium bis(fluorosulfonyl)imide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, more preferably 1-butyl-3-methylpyridinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide.
[0125] Ionic liquids may be commercially available ones or synthesized ones. Examples of the synthesis method of ionic liquids include common synthesis methods such as the halide method, hydroxide method, acid ester method, complex formation method, and neutralization method, as described in the literature "Ionic Liquids - The Forefront and Future of Development -" published by CMC Publishing Co., Ltd.
[0126] <A-3-e. Fatty Acid Ester> The adhesive composition preferably contains a fatty acid ester. The fatty acid ester may be only one kind or two or more kinds. By the adhesive composition containing a fatty acid ester, the surface protection film of the present invention can exhibit excellent light peelability while exhibiting excellent temporal stability of the peel strength.
[0127] The number average molecular weight Mn of the fatty acid ester is preferably 100 to 800, more preferably 150 to 700, still more preferably 200 to 600, still more preferably 250 to 500, particularly preferably 300 to 400, and most preferably 350 to 400. If the number average molecular weight Mn of the fatty acid ester is within the above range, the surface protection film of the present invention can exhibit excellent light peelability while exhibiting more excellent temporal stability of the peel strength.
[0128] As the fatty acid ester, any appropriate fatty acid ester can be employed as long as the effects of the present invention are not impaired. Examples of such fatty acid esters include polyoxyethylene bisphenol A laurate, butyl stearate, 2-ethylhexyl palmitate, 2-ethylhexyl stearate, behenic acid monoglyceride, cetyl 2-ethylhexanoate, isopropyl myristate, isopropyl palmitate, cholesteryl isostearate, lauryl methacrylate, methyl coconut fatty acid, methyl laurate, methyl oleate, methyl stearate, myristyl myristate, octyldodecyl myristate, pentaerythritol monooleate, pentaerythritol monostearate, pentaerythritol tetrapalmitate, stearyl stearate, isotridecyl stearate, triglyceride 2-ethylhexanoate, butyl laurate, and octyl oleate.
[0129] When the adhesive composition contains a fatty acid ester, the content ratio of the fatty acid ester is preferably 0.01 to 50 parts by weight, more preferably 0.1 to 40 parts by weight, still more preferably 0.5 to 30 parts by weight, particularly preferably 1 to 20 parts by weight, and most preferably 5 to 15 parts by weight, based on 100 parts by weight of the base polymer. If the content ratio of the fatty acid ester is within the above range with respect to 100 parts by weight of the base polymer, the surface protection film of the present invention can exhibit excellent light peelability and more excellent temporal stability of the peel strength.
[0130] <A-3-f. Other Components> The pressure-sensitive adhesive composition may contain any other appropriate components as long as they do not impair the effects of the present invention. Examples of such other components include solvents, catalysts, silicone additives such as modified silicone oil, crosslinking accelerators, silane coupling agents, antioxidants, UV absorbers, light stabilizers, resin components, tackifiers, crosslinking retarders, inorganic fillers, organic fillers, metal powders, colorants (pigments, dyes, etc.), chain transfer agents, plasticizers, softeners, antioxidants, conductive agents, foil-like materials, surface lubricants, leveling agents, corrosion inhibitors, heat stabilizers, polymerization inhibitors, and lubricants.
[0131] <A-4. Manufacturing of surface protection films> The surface protection film according to the embodiment of the present invention can be produced by any suitable method. (1) A method (direct method) in which a pressure-sensitive adhesive composition is directly applied to a substrate film serving as any suitable substrate layer (for example, the substrate layer in a surface protection film according to an embodiment of the present invention), and if necessary, heated and dried to form a pressure-sensitive adhesive layer on the substrate layer; (2) A method (transfer method) in which a pressure-sensitive adhesive composition is applied to the surface (release surface) of a release liner, and if necessary, heated and dried, and the pressure-sensitive adhesive layer formed on the surface of the release liner is laminated to a substrate film serving as any appropriate substrate layer (for example, the substrate layer in a surface protection film according to an embodiment of the present invention), thereby transferring the pressure-sensitive adhesive layer onto the substrate layer; (3) A method of forming and applying a pressure-sensitive adhesive composition onto a substrate layer by extrusion; (4) A method of extruding a substrate layer and a pressure-sensitive adhesive layer in two or more layers. (5) A method of laminating a single layer of an adhesive layer onto a substrate layer, or a method of laminating a double layer of an adhesive layer together with a laminate layer, (6) A method of laminating a pressure-sensitive adhesive layer and a base layer-forming material such as a film or laminate layer in two or more layers. From the viewpoint of anchoring properties of the pressure-sensitive adhesive layer, the direct method (1) or the transfer method (2) is preferred, and the direct method (1) is more preferred.
[0132] As the coating method, various conventionally known methods such as roll coating, gravure roll coating, reverse roll coating, kiss roll coating, dip roll coating, bar coating, roll brush coating, spray coating, knife coating, air knife coating, comma coating, direct coating, and die coating can be appropriately used.
[0133] ≪≪B.Applications≫≫ The surface protective film according to the embodiment of the present invention is typically attached to the exposed surface of an optical or electronic component to prevent the surface of the optical or electronic component from being scratched during processing, assembly, inspection, transportation, etc. in the manufacturing process of the optical or electronic component. The optical component of the present invention has the surface protective film of the present invention attached thereto. The electronic component of the present invention has the surface protective film of the present invention attached thereto. [Example]
[0134] The present invention will be specifically described below using examples, but the present invention is not limited to these examples. The test and evaluation methods used in the examples are as follows. The term "parts" means "parts by weight" unless otherwise specified, and the term "%" means "% by weight" unless otherwise specified.
[0135] <Surface free energy of adhesive layer surface with respect to diiodomethane> The surface protection film with the release liner removed was cut to a size of 50 mm wide and 100 mm long, and the adhesive layer surface was placed facing up and fixed to a contact angle meter (Kyowa Interface Science Co., Ltd., model "CA-X") to measure the contact angle by dropping 2.0 μL of water onto the adhesive layer surface. Next, using the same procedure, 2.0 μL of diiodomethane was dropped and the contact angle was measured. The surface free energy of the adhesive layer surface with respect to diiodomethane was calculated using the Owens-Wendt method from the contact angle values of these two liquids.
[0136] <Residual sulfur content on the surface of acrylic sheets> The release liner was removed and the adhesive layer of the surface protection film (10 mm × 10 mm) was attached to the surface of an acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation) using a 2 kg hand roller, rolling it back and forth once, and then left to stand at an ambient temperature of 23°C for 30 minutes. After peeling off the surface protection film from the surface of an acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation), narrow scan measurement was performed on the peeled area using ESCA, and the element ratio (atomic %) was calculated. The measurement conditions were as follows: Equipment: ULVAC-PHI "Quantera SXM" X-ray source: Monochrome Al Ka X Ray setting:100μmφ[15kV,25W] Photoelectron take-off angle: 45 degrees to the sample surface Neutralization conditions: Use of a neutralization gun and an Ar ion gun (neutralization mode) Bond energy correction: The peak due to the CC bond in the C1s spectrum is corrected to 285.0 eV Detection limit: 0.1 atomic%
[0137] <Measurement of peel strength A from acrylic plate (after leaving at 23°C for 30 minutes)> The adhesive layer of the surface protection film (25 mm wide x 140 mm long) from which the release liner had been removed was attached to the surface of an acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation) using a 2 kg hand roller in one stroke, and left to stand at an ambient temperature of 23°C for 30 minutes. The evaluation sample obtained as described above was measured using a tensile tester. Shimadzu Corporation's Autograph AG-Xplus HS 6000 mm / min High-Speed Model (AG-50NX plus) was used as the tensile tester. The evaluation sample was set in the tensile tester, and the tensile test was started. Specifically, the load when peeling the surface protection film from the acrylic plate was measured, and the average load was defined as the peel force A of the surface protection film from the acrylic plate. The tensile test conditions were a test environment temperature of 23°C, a peel angle of 180°, and a peel speed (pulling speed) of 300 mm / min.
[0138] <Measurement of peel strength B from acrylic plate (after leaving at 50°C for 1 day)> The adhesive layer of the surface protection film (25 mm wide x 140 mm long) from which the release liner had been removed was attached to the surface of an acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation) using a 2 kg hand roller in one stroke, and left at an ambient temperature of 50°C for one day. The evaluation sample obtained as described above was measured using a tensile tester. Shimadzu Corporation's Autograph AG-Xplus HS 6000 mm / min High-Speed Model (AG-50NX plus) was used as the tensile tester. The evaluation sample was set in the tensile tester, and the tensile test was started. Specifically, the load when peeling the surface protection film from the acrylic plate was measured, and the average load was defined as the peel force B of the surface protection film from the acrylic plate. The tensile test conditions were a test environment temperature of 23°C, a peel angle of 180°, and a peel speed (pulling speed) of 300 mm / min.
[0139] <Rate of increase in peeling force over time> The rate of increase in peel force over time from peel force A to peel force B was calculated using the following formula. Peel force increase rate over time (%) = (peel force B / peel force A) x 100 (%)
[0140] <Residual adhesive strength to acrylic board> The adhesive layer of a surface protection film was applied to the entire surface of an acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation) using a hand roller. After storing the film at 23°C for 24 hours, the film was peeled off at a peel angle of 180° and a peel speed (pulling speed) of 300 mm / min. Adhesive tape (Nitto Denko Corporation's "No. 31B" tape, 19 mm wide and cut to a length of 150 mm, with a substrate thickness of 25 μm) was applied to the acrylic plate surface using a 2 kg roller at 23°C. After leaving the tape at 23°C for 30 minutes, the tape was peeled off at a peel angle of 180° and a pulling speed of 300 mm / min using a tensile tester (Shimadzu Corporation's "Autograph AG-Xplus HS 6000 mm / min High-Speed Model (AG-50NX plus)"). The adhesive strength (C) was measured. On the other hand, the adhesive tape was similarly applied to the surface of an acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation) that had not been subjected to the above-mentioned release treatment, and after leaving it at a temperature of 23°C for 30 minutes, the adhesive tape was peeled off from the surface of the acrylic plate at a peel angle of 180° and a peel speed of 300 mm / min at a temperature of 23°C, and the adhesive strength D was measured. The residual adhesive strength to the acrylic plate was calculated using the following formula. Residual adhesive strength to acrylic board (%) = (adhesive strength C / adhesive strength D) x 100 (%)
[0141] <Charged voltage when peeling off acrylic sheet> The surface protection film from which the release liner had been removed was cut to a size of 70 mm wide and 100 mm long, and was pressed onto the surface of an acrylic plate (Acrylite, manufactured by Mitsubishi Chemical Corporation) using a 2 kg hand roller in one stroke back and forth so that one end of the surface protection film in the longitudinal direction protruded 30 mm beyond the edge of the acrylic plate. This sample was left for one day in an environment of 23°C and 50% RH, and then set in a predetermined position on a sample fixing table with a height of 20 mm. The end of the surface protection film extending 30 mm beyond the edge of the acrylic plate was fixed to an automatic winding machine, and the acrylic plate was peeled off at a peel angle of 150° and a peel speed of 30 m / min. The potential generated on the surface of the acrylic plate during this process was measured using a potential meter (manufactured by Shishido Electrostatic Corporation, model "STATIRON DZ-4") fixed at a position 30 mm above the center of the acrylic plate, and the obtained potential was taken as the peel electrification voltage relative to the acrylic plate. Measurements were performed in an environment of 23°C and 50% RH.
[0142] <Surface resistance value> The surface protection film was cut to a size of 50 mm x 50 mm, and after peeling off the release liner, the adhesive layer side was pressed against a terminal at 10 V for 10 seconds using Trek Japan's Model 152P-2P to measure the surface resistance.
[0143] [Production Example 1]: Preparation of coating material for forming antistatic layer 100 parts by weight of a 25% aqueous solution of polyester resin (manufactured by Toyobo Co., Ltd., trade name "Vylonal MD-1480") as a binder resin, 20 parts by weight of a conductive polymer, and 5 parts by weight of a melamine-based crosslinking agent (manufactured by Sumitomo Chemical Co., Ltd., trade name "Sumimal M-50W") were added to a water / ethanol (1 / 1 (by weight)) mixed solvent and stirred for about 20 minutes to thoroughly mix. In this way, a coating material for forming an antistatic layer with a solids content of about 0.4% was prepared. The conductive polymer used was an aqueous solution (Bytron P, manufactured by HC Stark) containing 0.5% poly(3,4-ethylenedioxythiophene) (PEDOT) and 0.8% polystyrene sulfonate (weight average molecular weight 150,000) (PSS).
[0144] [Production Example 2]: Preparation of substrate (a) with antistatic layer A 75 μm-thick transparent polyethylene terephthalate (PET) film (product name "T100-75S," 75 μm thick, manufactured by Mitsubishi Chemical Corporation) was prepared. The antistatic layer-forming coating material prepared in Production Example 1 was applied to one side of this PET film using a bar coater, and the film was dried by heating at 130°C for 2 minutes. In this way, a substrate (a) with an antistatic layer was prepared, having a 30 nm-thick transparent antistatic layer on one surface of the PET film.
[0145] [Production Example 3]: Preparation of substrate (b) with antistatic layer A 75 μm-thick transparent polyethylene terephthalate (PET) film (product name "T100-75S," 75 μm thick, manufactured by Mitsubishi Chemical Corporation) was prepared. The antistatic layer-forming coating material prepared in Production Example 1 was applied to both sides of this PET film using a bar coater, and the film was dried by heating at 130°C for 2 minutes. In this way, a substrate (b) with an antistatic layer was prepared, having 30 nm-thick transparent antistatic layers on both surfaces of the PET film.
[0146] [Production Example 4]: Preparation of urethane prepolymer A polymerization experiment apparatus equipped with a 1 L round-bottom separable flask, a separable cover, a separatory funnel, a thermometer, a nitrogen inlet tube, a Liebig condenser, a vacuum seal, a stirring rod, and a stirring blade was charged with 197 g of polypropylene glycol (product name "Sannyx PP-2000", manufactured by Sanyo Chemical Industries, Ltd.), 197 g of polyester polyol (product name "Kuraray Polyol P-2010", manufactured by Kuraray Co., Ltd.), 110 g of toluene (manufactured by Tosoh Corporation) as a solvent, and 0.041 g of dibutyltin(IV) dilaurate (manufactured by Wako Pure Chemical Industries, Ltd.) as a catalyst, and the mixture was purged with nitrogen at room temperature for 1 hour while stirring. Then, under nitrogen flow and stirring, 33.5 g of hexamethylene diisocyanate (product name "HDI", manufactured by Tosoh Corporation) was added. The solution temperature in the experimental apparatus was maintained at 90±2°C in a water bath and held for 4 hours. Then, 44 g of polypropylene glycol (product name "GP1000", manufactured by Sanyo Chemical Industries, Ltd.) was added. The solution temperature in the experimental apparatus was maintained at 90±2°C in a water bath and held for 2 hours. Then, 25.4 g of hexamethylene diisocyanate (product name "HDI", manufactured by Tosoh Corporation) was added. The solution temperature in the experimental apparatus was maintained at 90±2°C in a water bath and held for 2 hours. This yielded a solution of urethane prepolymer A. During the polymerization, toluene was added dropwise as needed to control the temperature and prevent a decrease in stirrability due to increased viscosity. The total amount of toluene added was 380 g. The solids concentration of the urethane prepolymer A solution was 50 wt%.
[0147] Example 1 A urethane-based pressure-sensitive adhesive composition was obtained by diluting 100 parts by weight of urethane prepolymer A, 4.0 parts by weight of an isocyanate compound (Coronate HX:C / HX, manufactured by Nippon Polyurethane Co., Ltd.) as a crosslinking agent, 0.3 parts by weight of Megafac F-571 (manufactured by DIC Corporation, a fluorine-containing, hydrophilic, and lipophilic group-containing oligomer, surface tension of 24.8 mN / m when made into a 0.1% toluene solution) as a fluorine-based oligomer, 0.5 parts by weight of Irganox 1010 (manufactured by BASF) as an antioxidant, 0.3 parts by weight of Elexcel AS110 (manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) as an antistatic agent, and 10 parts by weight of Salacos 913 (isotridecyl isononanoate, molecular weight = 341, manufactured by The Nisshin Oillio Group, Ltd.) as a fatty acid ester with ethyl acetate to a total solids content of 50% by weight. The resulting urethane-based pressure-sensitive adhesive composition was applied to the antistatic layer-attached substrate (b) obtained in Production Example 3 to a dry thickness of 75 μm, and then cured and dried at a drying temperature of 130°C for 2 minutes. The silicone-treated surface of a 25 μm-thick release liner (trade name "MRF25", thickness 25 μm, manufactured by Mitsubishi Chemical Corporation) made of polyester resin and silicone-treated on one side was then laminated to the surface of the resulting pressure-sensitive adhesive layer to obtain a surface protection film (1). The film was aged at room temperature for 5 days and then evaluated. The release liner was peeled off immediately before evaluation, if necessary. The results are shown in Tables 1 and 2.
[0148] Example 2 A surface protection film (2) was obtained in the same manner as in Example 1, except that the amount of Elexcel AS110 used as the ionic compound was changed to 0.5 parts by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0149] Example 3 A surface protection film (3) was obtained in the same manner as in Example 1, except that the amount of Elexcel AS110 used as the ionic compound was changed to 1.0 part by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0150] Example 4 A surface protection film (4) was obtained in the same manner as in Example 1, except that 0.3 parts by weight of CIL-312 (manufactured by Nippon Carlit Co., Ltd.) was used as the ionic compound, as shown in Table 1. The results are shown in Tables 1 and 2.
[0151] Example 5 A surface protection film (5) was obtained in the same manner as in Example 4, except that the amount of CIL-312 used as the ionic compound was changed to 0.5 parts by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0152] Example 6 A surface protection film (6) was obtained in the same manner as in Example 4, except that the amount of CIL-312 used as the ionic compound was changed to 1.0 part by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0153] Example 7 A surface protection film (7) was obtained in the same manner as in Example 1, except that the amount of the isocyanate compound used as a crosslinking agent was changed to 3.0 parts by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0154] Example 8 A surface protection film (8) was obtained in the same manner as in Example 7, except that the amount of Elexcel AS110 used as the ionic compound was changed to 1.0 part by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0155] Example 9 A surface protection film (9) was obtained in the same manner as in Example 2, except that the amount of Megafac F-571 used as the fluorine-based oligomer was changed to 0.5 parts by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0156] Example 10 A surface protection film (10) was obtained in the same manner as in Example 2, except that the amount of Megafac F-571 used as the fluorine-based oligomer was changed to 0.1 parts by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0157] Example 11 A surface protection film (11) was obtained in the same manner as in Example 2, except that 10.0 parts by weight of Exepar IPP (isopropyl palmitate, molecular weight = 299, manufactured by Kao Corporation) was used as the fatty acid ester, as shown in Table 1. The results are shown in Tables 1 and 2.
[0158] Example 12 A surface protection film (12) was obtained in the same manner as in Example 2, except that 10.0 parts by weight of Exepal IPM (isopropyl myristate, molecular weight = 270, manufactured by Kao Corporation) was used as the fatty acid ester, as shown in Table 1. The results are shown in Tables 1 and 2.
[0159] Example 13 A surface protection film (13) was obtained in the same manner as in Example 2, except that no fatty acid ester was used, as shown in Table 1. The results are shown in Tables 1 and 2.
[0160] Example 14 A surface protection film (14) was obtained in the same manner as in Example 1, except that no ionic compound was used, as shown in Table 1. The results are shown in Tables 1 and 2.
[0161] Example 15 A surface protection film (15) was obtained in the same manner as in Example 2, except that the amount of Megafac F-571 used as the fluorine-based oligomer was changed to 1.0 part by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0162] Example 16 A surface protection film (16) was obtained in the same manner as in Example 2, except that 0.3 parts by weight of Megafac F-563 (a fluorine-containing, lipophilic group-containing oligomer, surface tension of 20.2 mN / m when made into a 0.1% toluene solution) was used as the fluorine-containing oligomer, as shown in Table 1. The results are shown in Tables 1 and 2.
[0163] Example 17 A surface protection film (17) was obtained in the same manner as in Example 2, except that 0.3 parts by weight of Megafac F-477 (manufactured by DIC Corporation, oligomer containing fluorine-containing groups, hydrophilic groups, and lipophilic groups, surface tension of 26.4 mN / m when made into a 0.1% toluene solution) was used as the fluorine-containing oligomer, as shown in Table 1. The results are shown in Tables 1 and 2.
[0164] Comparative Example 1 A surface protective film (C1) was obtained in the same manner as in Example 1, except that a urethane-based pressure-sensitive adhesive composition was prepared without using either an ionic compound or a fluorine-based oligomer, and the composition was applied to the PET film side of the antistatic layer-equipped substrate (a) obtained in Production Example 2 so as to have a thickness of 75 μm after drying, instead of being applied to the antistatic layer-equipped substrate (b) obtained in Production Example 3 so as to have a thickness of 75 μm after drying, as shown in Table 1. The results are shown in Tables 1 and 2.
[0165] Comparative Example 2 A surface protective film (C2) was obtained in the same manner as in Example 3, except that a urethane-based pressure-sensitive adhesive composition was prepared without using a fluorine-based oligomer and applied to the PET film side of the antistatic layer-equipped substrate (a) obtained in Production Example 2 so as to have a thickness of 75 μm after drying, instead of being applied to the antistatic layer-equipped substrate (b) obtained in Production Example 3 so as to have a thickness of 75 μm after drying, as shown in Table 1. The results are shown in Tables 1 and 2.
[0166] Comparative Example 3 A surface protective film (C3) was obtained in the same manner as in Example 3, except that instead of applying the coating to the substrate (b) with an antistatic layer obtained in Production Example 3 so as to have a thickness of 75 μm after drying, the coating was applied to the PET film side of the substrate (a) with an antistatic layer obtained in Production Example 2 so as to have a thickness of 75 μm after drying, as shown in Table 1. The results are shown in Tables 1 and 2.
[0167] Comparative Example 4 A surface protection film (C4) was obtained in the same manner as in Comparative Example 3, except that the amount of Elexcel AS110 used as the ionic compound was changed to 3.0 parts by weight as shown in Table 1. The results are shown in Tables 1 and 2.
[0168] [Table 1]
[0169] [Table 2]
[0170] Examples 18 to 34 For each of the surface protection films (1) to (17) obtained in Examples 1 to 17, the separator was peeled off, and the pressure-sensitive adhesive layer side was attached to a polarizing plate (manufactured by Nitto Denko Corporation, product name "TEG1465DUHC"), which is an optical component, to obtain an optical component with the surface protection film attached.
[0171] Examples 35 to 51 For each of the surface protection films (1) to (17) obtained in Examples 1 to 17, the separator was peeled off, and the adhesive layer side was attached to a conductive film (manufactured by Nitto Denko Corporation, product name "ELECRYSTA V270L-TFMP"), which is an electronic component, to obtain an electronic component with a surface protection film attached. [Industrial Applicability]
[0172] The surface protective film of the present invention can be used for any suitable application, and is preferably used in the fields of optical members and electronic members. [Explanation of symbols]
[0173] 1 Base material layer 2 Antistatic layer 3. Adhesive layer 10 Surface protection film
Claims
1. A surface protection film having a base layer, an antistatic layer, and a pressure-sensitive adhesive layer in this order, the antistatic layer comprises a binder resin and a conductive polymer; the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is formed from a pressure-sensitive adhesive composition, The pressure-sensitive adhesive composition comprises a base polymer and a fluorine-based compound, The base polymer is a urethane prepolymer. Surface protection film.
2. The surface protective film according to claim 1 , wherein the pressure-sensitive adhesive composition comprises a fatty acid ester.
3. The surface protective film according to claim 2, wherein the fatty acid ester has a molecular weight of 300 to 400.
4. The surface protective film according to claim 1 , wherein the pressure-sensitive adhesive composition comprises an ionic compound.
5. The surface protection film according to claim 1, wherein the amount of residual sulfur on the surface of the acrylic plate is less than 0.1 atomic % after the pressure-sensitive adhesive layer side of the surface protection film is attached to the surface of an acrylic plate, the surface protection film is left at 23°C for 30 minutes, and the surface protection film is then peeled off from the surface of the acrylic plate.
6. 5. The surface protective film according to claim 4, wherein the content of the ionic compound is 0.4 parts by weight to 3.0 parts by weight based on 100 parts by weight of the base polymer.
7. The surface protective film according to claim 4, wherein the ionic compound has a molecular weight of 200 to 350.
8. The pressure-sensitive adhesive composition contains a polyfunctional isocyanate compound, and the equivalent ratio of the NCO group of the polyfunctional isocyanate compound to the OH group of the urethane prepolymer is 1.6 to 2.5, expressed as NCO group / OH group. The surface protective film according to claim 1.
9. The surface free energy of the surface of the pressure-sensitive adhesive layer with respect to diiodomethane is 3.5 mJ / m 2 ~7.0 mJ / m 2 The surface protection film according to claim 1 ,
10. 2. The surface protective film according to claim 1, wherein the content of the fluorine-based compound is 0.1 to 3.0 parts by weight based on 100 parts by weight of the base polymer.
11. An optical member having the surface protective film according to any one of claims 1 to 10 attached thereto.
12. An electronic component having the surface protective film according to any one of claims 1 to 10 attached thereto.